Influence of climatic variables on maize grain yield and its components by adjusting the sowing date - Wu, Wenming; Yue, Wei; Bi, Jianjian; Zhang, Lin; Xu, Dafeng; Peng, Chen; Chen, Xiang; Wang, Shiji (Frontiers in Plant Science, 2024)
Yield and its components are greatly affected by climate change. Adjusting the sowing date is an effective way to alleviate the adverse effects and adapt to climate change. Aiming to determine the optimal sowing date of summer maize and clarify the contribution of climatic variables to grain yield and its components, a consecutive four-year field experiment was conducted from 2016 to 2019 with four sowing dates at 10-day intervals from 5 June to 5 July. Analysis of historical meteorological data showed that more solar radiation (SR) was distributed from early June to mid-August, and the maximum temperature (Tmax) > 32 ℃ appeared from early July to late August, which advanced and lasted longer in 1991-2020 relative to 1981-1990. Additionally, the precipitation was mainly distributed from early June to late July. The climate change in the growing season of summer maize resulted in optimal sowing dates with higher yields and yield stability ranging from 5 June to 15 June, mainly because of the higher kernel number per ear and 1000-grain weight. The average contribution of kernel number per ear to grain yield was 58.7%, higher than that of 1000-grain weight (41.3%). Variance partitioning analysis showed that SR in 15 d pre-silking to 15 d post-silking (SS) and silking to harvest (SH) stages significantly contributed to grain yield by 63.1% and 86.4%. The extreme growing degree days > 32 ℃ (EDD), SR, precipitation, and diurnal temperature range (DTR) contributed 20.6%, 22.9%, 14.5%, and 42.0% to kernel number per ear in the SS stage, respectively. Therefore, we concluded that the early sowing dates could gain high yield and yield stability due to the higher SR in the growing season. Meanwhile, due to the decreasing trend in SR and increasing Tmax trend in this region, in the future, new maize variety with high-temperature resistance, high light efficiency, shade-tolerant, and medium-season traits need to be bred to adapt to climate change and increased grain yield.